On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae) - Simó, Miguel; Lise, Arno A.; Pompozzi, Gabriel; Laborda, Álvaro (Zootaxa, 2017)
Three species of the genus Allocosa Banks, 1900 from southern South America are redescribed: Allocosa alticeps (Mello-Leitão, 1944), A. brasiliensis (Petrunkevitch, 1910) and A. senex (Mello-Leitão, 1945). The female of A. senex is described for the first time and the species is revalidated. A new species, A. marindia sp. nov. from southern Uruguay and southern Brazil is described. The new species is distinguished by the flattened terminal apophysis of the male bulb and the conspicuous pointed projections on the posterior margin of the female epigynum. The species inhabits in sandy estuarine and oceanic coasts with psammophile vegetation.